Moderasi Beragama dalam Tradisi Pendidikan Islam Melayu: Antara Normativitas dan Praktik Sosial - Ari Koswara; Eprianto; Abdullah Idi; Abdillah Asmara (WISE Pendidikan Indonesia, 2026)
This article examines religious moderation in the Malay Islamic educational tradition by analyzing the relationship between Islamic normativity, social practice, and local cultural wisdom. The study responds to the limited discussion that connects the normative concept of wasatiyyah with everyday educational practices in pesantren, surau, and Malay Islamic learning communities. This research employed a qualitative descriptive-interpretive literature review by examining classical Islamic texts, contemporary peer-reviewed studies, policy documents on religious moderation, and studies on Malay Islamic culture, pesantren, and local wisdom published mainly between 2018 and 2026. The findings show that religious moderation in Malay Islamic education is constructed through three interrelated dimensions: normative values such as tawassuth, tasamuh, tawazun, and i’tidal; social practices such as teacher exemplarity, dialogical learning, respect for difference, and community-based education; and local wisdom that functions as a cultural filter against exclusivist and transnational religious narratives. The study also finds that digital disruption challenges traditional religious authority and requires Malay Islamic educational institutions to strengthen religious moderation through contextual pedagogy, culturally grounded leadership, and digital literacy. The novelty of this article lies in its integrative reading of religious moderation as a dialectical process between Islamic normativity and Malay social practice. The study implies that strengthening religious moderation in Islamic education should not rely solely on formal curriculum, but also on institutional culture, local wisdom, teacher role modeling, and responsible digital engagement.